Red blood cell exchange in children and adolescents with sickle cell disease. (April 2019) - Merlin, E.; Hequet, O.; Kanold, J.
Abstract: Automatic red blood cell exchange i.e. using devices (RBCX) has become a standard therapy to remove abnormal red blood cells (RBC) in adults and children affected by sickle cell disease (SCD). This treatment is performed both in emergency to treat acute complications and through a regular program of RBCX to prevent the recurrence of complications. However, small children, i.e. those with a low body weight, height and total blood volume, are at risk of relative hypovolemia and metabolic complications during the procedure. Moreover, the peripheral venous access is limited among young children, which requires alternative short- or long-term venous access. These two main limiting factors necessitate adaptations of the procedures and subsequent monitoring during and after the sessions. However, performing RBCX in children requires other adaptations and cautions that must be considered. Our review summarizes the limits, safety precautions and the adaptations of the techniques to ensure RBCX in children.